PELATIHAN MEMBUAT ECOBRICK UNTUK GENERASI MUDA DALAM MENINGKATKAN KEPEDULIAN KEBERSIHAN LINGKUNGAN DI PEDESAAN - Hidayatullah, Syarif; Suteja, Suteja; Huda, Ahmad Akromul; Sari, Nasmi Herlina; Tawaqqal, Akbar (Jurnal Abdi Insani, 2025)
The issue of plastic waste in rural communities has become an urgent environmental concern due to limited waste management facilities and low public awareness of the impacts of plastic pollution. The massive use of plastics without proper disposal systems has led to the accumulation of waste that contaminates the environment. One practical and educational solution that can be implemented is the production of ecobricks, which involves processing plastic waste into environmentally friendly building materials. This activity aimed to enhance the knowledge, awareness, and skills of young people aged 10–16 years in Ambung Village, East Masbagik District, in managing plastic waste through ecobrick-making training. The implementation method consisted of three stages: socialization, training, and evaluation. The socialization stage involved an interactive lecture on the dangers of plastic waste, followed by hands-on practice in making ecobricks using used plastic bottles. Evaluation was conducted using pre-test and post-test instruments to measure participants’ understanding of the reduce, reuse, recycle (3R) concept. The results showed a significant increase in participants’ knowledge levels, with an average pre-test score of 51.5 and a post-test score of 84.5, representing an improvement of 63.4%. Participants gained a better understanding of plastic waste management processes, were able to produce ecobricks independently, and were motivated to apply this knowledge at home while encouraging family members and peers to participate. Moreover, the activity fostered a sense of collaboration and creativity among participants by transforming plastic waste into functional products such as flower pots and garden benches. It can be concluded that ecobrick-making training effectively increased ecological awareness, knowledge, and practical skills among young people in plastic waste management, serving as an initial step toward a cleaner and more sustainable village environment.